STARTER FEED PROCESSING FOR SUPPORTING PIG FATTENING IN PARTNERSHIP WITH “SEHATI” FARMER’S GROUP OF TUATUKA VILLAGE - Stormy Vertygo; Helda Helda; Cytske Sabuna; Yelly M. Mulik; Redempta Wea; Andy Yumima Ninu; Defrys Rudolf Tulle (Jurusan Peternakan Politeknik Pertanian Negeri Kupang, 2021)
Since the establishment of a Memorandum of Understanding (MoU) between the Department of Animal Husbandry-State Agricultural Polytechnic of Kupang (Politani Kupang) and the farmer’s group of Tuatuka village in East Kupang district of Kupang regency, the department have carried out various and gradual community service programs at the location. However, problems the farmers are still facing in breeding their pig livestock are: limited capital to increase business scale and availability of feed and the low quality of livestock breeds. As a continuation of the activities that have been initiated previously, the Animal Feed Technology (TPT) study program initiated to help partner farmers by building a system of partnership cooperation that can help overcome some of the problems faced, especially related to the availability of animal feed. Based on the situation analysis that has been carried out at the location, the study program has determined the topic of the community service which is: